2018
DOI: 10.1002/cne.24464
|View full text |Cite
|
Sign up to set email alerts
|

Post‐crossing segment of dI1 commissural axons forms collateral branches to motor neurons in the developing spinal cord

Abstract: The dI1 commissural axons in the developing spinal cord, upon crossing the midline through the floor plate, make a sharp turn to grow rostrally. These post-crossing axons initially just extend adjacent to the floor plate without entering nearby motor columns. However, it remains poorly characterized how these post-crossing dI1 axons behave subsequently to this process. In the present study, to address this issue, we examined in detail the behavior of post-crossing dI1 axons in mice, using the Atoh1 enhancer-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
(111 reference statements)
4
4
0
Order By: Relevance
“…We find some interesting features of locally-projecting Atoh1-lineage neurons and compare and contrast our findings with those of a previous study using an Atoh1-enhancer driving CRE recombinase electroporated into mouse embryos (Kaneyama and Shirasaki, 2018). First, we find that thoracolumbar Atoh1-lineage neurons project mostly locally, consistent with the findings by Kaneyama and Shiraskai, who found that crossing dI1 axons are intersegmental with only a few traveling far from the soma.…”
Section: Local Projections Of Atoh1-lineage Neuronssupporting
confidence: 88%
“…We find some interesting features of locally-projecting Atoh1-lineage neurons and compare and contrast our findings with those of a previous study using an Atoh1-enhancer driving CRE recombinase electroporated into mouse embryos (Kaneyama and Shirasaki, 2018). First, we find that thoracolumbar Atoh1-lineage neurons project mostly locally, consistent with the findings by Kaneyama and Shiraskai, who found that crossing dI1 axons are intersegmental with only a few traveling far from the soma.…”
Section: Local Projections Of Atoh1-lineage Neuronssupporting
confidence: 88%
“…Goat polyclonal antibodies raised against Lhx2 (1:200, Santa Cruz #sc‐19,344), Robo3 (1:200, R&D Systems #AF3076), transient axonal glycoprotein (TAG)‐1 (1:200, R&D Systems #AF4439), tropomyosin receptor kinase (Trk)‐A (1:200, R&D Systems #AF1056), TrkB (1:50, R&D Systems #AF1494), and TrkC (1:40, R&D Systems #AF1404) were used. The anti‐Lhx2 antibody () was raised against a C‐terminus peptide of Lhx2 of human origin and has been used to specifically label Lhx2‐positive dI1 neurons in the developing spinal cord (Kaneyama & Shirasaki, ). The anti‐Robo3 antibody () was raised against the extracellular domain of recombinant human Robo3, and specificity was validated in Robo3 conditional knockout mutants (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Atoh1 -lineage neurons have classically been subdivided into a contralaterally-projecting Medial (dI1c) and ipsilaterally-projecting Lateral (dI1i) population (Bermingham et al, 2001; Wilson et al, 2008). However, recent anatomical studies challenge this view with at least a subset of Atoh1 -lineage Lateral cells projecting potentially both ipsi- and contralaterally (Kaneyama and Shirasaki, 2018; Pop et al, 2022). Without unique molecular markers to distinguish subsets of the Atoh1 -lineage population, we set out to evaluate whether the Medial and Lateral cells had distinct electrophysiological signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Atoh1 Medial cells, also known as dI1c, are thought to be contralaterally-projecting while Atoh1 Lateral cells, also known as dI1i, are ipsilaterally-projecting. However, recent evidence suggests that subsets of the Atoh1 Lateral are also contralaterally-projecting (Kaneyama and Shirasaki, 2018; Pop et al, 2022). Therefore, using whole cell patch clamp and molecular genetic tools in mice, we set out to determine if Atoh1 -lineage Medial and Lateral neurons had distinguishing electrophysiological signatures.…”
Section: Introductionmentioning
confidence: 99%